Induction of neutralizing antibody responses by AAV5-based vaccine for respiratory syncytial virus in mice - Ma, Gangyuan; Xu, Zeping; Li, Chinyu; Zhou, Feng; Hu, Bobo; Guo, Junwei; Ke, Changwen; Chen, Liqing; Zhang, Guilin; Lau, Hungyan; Pan, Hudan; Chen, Xixin; et al. (Frontiers in Immunology, 2024)
Introduction Respiratory Syncytial Virus (RSV) is a significant cause of respiratory illnesses worldwide, particularly in infants and elderly individuals. Despite the burden RSV imposes, effective preventive measures are limited. The research application of adeno-associated virus (AAV) in vaccine platforms has been expanding, and its potential in prevention and treatment has garnered much attention. Methods In this study, we explored the potential application of a recombinant adeno-associated virus 5 (rAAV5) vector-based RSV vaccine, focusing on the expression of the pre-fusion (Pre-F) protein structure. Through intramuscular immunization in mice. The immunogenicity of the vaccine was evaluated in Balb/c mice immunized intramuscularly and intranasal, respectively. Results The rAAV5-RSV-Fm vaccine demonstrated positive humoral and induced antibody titers against RSV strains A and B for up to 120 days post-immunization. Notably, intranasal administration also elicited protective antibodies. Characterization studies confirmed the ability of the vac-cine to express the Pre-F protein and its superior immunogenicity compared to that of full-length F protein. Conclusion These findings underscore the potential application of rAAV5 vector platforms in RSV vaccine development and further investigation into their protective efficacy is warranted.